2022
DOI: 10.3389/fimmu.2022.911779
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-to-Lymphocyte and Monocyte-to-Lymphocyte Ratios Are Independently Associated With the Severity of Autoimmune Encephalitis

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are biomarkers that may reflect inflammatory status in some immune-related diseases. This study aims to investigate the association of NLR and MLR with the severity and prognosis of autoimmune encephalitis (AE).MethodsA total of 199 patients diagnosed with AE in the First Affiliated Hospital of Zhengzhou University from October 2015 to October 2021 were retrospectively analyzed. The Clinical Assessment Scale for Autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…In our analysis, the mRS score upon admission was another prognostic factor. However, a previous study reported no association between the mRS score upon admission and prognosis ( 24 ). This conflicting result may be attributed to several reasons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our analysis, the mRS score upon admission was another prognostic factor. However, a previous study reported no association between the mRS score upon admission and prognosis ( 24 ). This conflicting result may be attributed to several reasons.…”
Section: Discussionmentioning
confidence: 96%
“…The previous study had a higher proportion of patients with anti-NMDAR encephalitis than our study. In the subgroup analysis, the mRS score upon admission was not associated with prognosis in patients with anti-NMDAR encephalitis but was associated with anti-leucine-rich glioma inactivated 1 encephalitis ( 24 ). Therefore, the impact of the mRS score upon admission on the prognosis may depend on the background disease.…”
Section: Discussionmentioning
confidence: 98%
“…Neben Neurodegenerationsmarkern werden inflammatorische Marker der Autoimmunenzephalitis erforscht. In 199 Patienten konnte gezeigt werden, dass sowohl die Neutrophilen-zu-Lymphozyten-Ratio als auch die Monozyten-zu-Lymphozyten-Ratio im Blut eine Progression der Erkrankung und einen schweren Verlauf bei einer Autoimmunenzephalitis anzeigen können [19]. Zudem wird an der Entwicklung von weiteren Biomarkern geforscht (z.…”
Section: Merkeunclassified
“…NLR, MLR and PLR are more accessible than inflammatory cytokines in clinical practice and scientific research, which have been used to predict progression and prognosis of many non-psychiatric diseases, such as hepatocellular carcinoma, gastric cancer, autoimmune encephalitis etc. ( 17 19 ). In recent years, there has been an increase in studies of psychiatric disorders involving these inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%